IDIOMS AND THEIR MEANINGS IN THE RUSSIAN LANGUAGE (American Journal of Pedagogical and Educational Research, 2024)
Phraseological units are stable combinations of words that have a meaning different from the meanings of individual words. In the Russian language, phraseological units play an important role in enriching speech, giving it expressiveness and emotional saturation. The article discusses the main types of phraseological units, their structure and meaning, as well as the role of phraseology in the development of the language.